TIME WELL SPENT? INVESTIGATING STUDENTS' USE OF SMARTPHONE ONLINE GAMES TO ACQUIRE ENGLISH VOCABULARY: A CASE STUDY AT SMK TELKOM MAKASSAR - Aryudha, Syawal; Jabu, Baso; Samtidar, Samtidar (JTechLP: Journal of Technology in Language Pedagogy, 2026)
The increasing use of English in smartphone-based online games opens up opportunities for students to acquire vocabulary through informal learning experiences. This study aims to analyze the influence of smartphone online games on English vocabulary mastery among students at SMK Telkom Makassar, particularly those participating in E-sports extracurricular activities. This study used a descriptive qualitative method with data collection through observation and interviews with students who actively play games such as Mobile Legends, Free Fire, and PUBG. The findings indicate that students spend 5–12 hours per day playing games, and through repeated exposure to game features, including instructions, character skills, system notifications, and player-to-player communication, they acquire new vocabulary contextually, such as loot, revive, spell, lane, and gather. The results confirm that smartphone online games can be a positive tool for vocabulary acquisition through repeated and meaningful language exposure, thus potentially being used as a supporting strategy in the language learning process in schools.